Bibliometric review of 1992–2022 publications on acupuncture for cognitive impairment - Zhou, Runjin; Xiao, Lu; Xiao, Wei; Yi, Yanfei; Wen, Huanhuan; Wang, Hongda (Frontiers in Neurology, 2022)
Objective To explore the development context, research hotspots, and frontiers of acupuncture therapy for cognitive impairment (CI) from 1992 to 2022 by visualization analysis. Methods Articles about acupuncture therapy for cognitive impairment were retrieved from the Web of Science Core Collection (WoSCC) until 1 March 2022. Basic information was collected by Excel 2007, and VOSviewer 1.6.17 was used to analyze the co-occurrence of countries, institutes, and authors. Co-citation maps of authors and references were analyzed by CiteSpace V.5.8.R3. In addition, CiteSpace was used to analyze keyword clusters and forecast research frontiers. Results A total of 279 articles were retrieved, including articles from 19 countries, 334 research institutes, and 101 academic journals. The most published country and institutes were the People's Republic of China (217) and the Fujian University of Traditional Chinese Medicine (40). Ronald C Petersen owned the highest co-citations (56). Keywords and co-cited references cluster showed the main research directions in this area, including “ischemic stroke,” “cerebral ischemia/reperfusion,” “mild cognitive impairment,” “Alzheimer's disease,” “vascular dementia,” “vascular cognitive impairment with no dementia,” “multi-infarct dementia,” “synaptic injury,” “functional MRI,” “glucose metabolism,” “NMDA,” “nuclear factor-kappa b pathway,” “neurotrophic factor,” “matrix metalloproteinase-2 (MMP-2),” “tumor necrosis factor-alpha,” “Bax,” “Caspase-3,” and “Noxa”. Trending keywords may indicate frontier topics, such as “randomized controlled trial,” “rat model,” and “meta-analysis.” Conclusion This research provides valuable information for the study of acupuncture. Diseases focus on mild cognitive impairment (MCI), Alzheimer's disease (AD), and vascular dementia (VaD). Tauopathies with hyperphosphorylation of Tau protein as the main lesions also need to be paid attention to. The development of functional magnetic resonance imaging (fMRI) will better explain the therapeutic effect of acupuncture treatment. The effect of acupuncture on a single point is more convincing, and acupuncture on Baihui (GV20) may be needed in the future. Finally, the implementation of high-quality multicenter randomized controlled trials (RCTs) requires increased collaboration among experts from multiple fields and countries.